Zeroth- and First-Order-Convertible Fiber Interleaving Filter - Kyongsoo Park; Yong Wook Lee (IEEE Photonics Journal)
In this paper, we propose a zeroth- and first-order-convertible fiber interleaving filter that has a frequency-interleaving capability in the zeroth- or first-order multiwavelength transmission spectrum. The proposed interleaving filter is a kind of polarization-diversity-loop-based comb filter composed of a polarization beam splitter, three half-wave plates (HWPs), and two polarization-maintaining fiber (PMF) segments, each of which is located between two adjacent HWPs. The HWP inserted between two PMF segments enables the interleaving filter to operate in the zeroth- or first-order transmission mode by adjusting the relative angular difference between the principal axes of two PMF segments. With the orientation angles of the three HWPs set as specific angles, first-order flat-top and narrow-band transmission spectra with a channel spacing of ∼0.792 nm could be obtained and be interleaved by controlling only the HWP between the two PMF segments. In particular, at other specific angle sets of the three HWPs, the zeroth-order transmission spectrum with the same channel spacing could be obtained, and their multiwavelength channels could be interleaved by adjusting only the orientation angle of the intermediary HWP. That is, a first-order comb spectrum could be converted into a zeroth-order one with the same fringe period, and each one could be interleaved through the proper control of the three HWP angles.